Nanoparticles in radiation oncology: From bench-side to bedside. Issue 2 (1st June 2016) - Rancoule, Chloé; Magné, Nicolas; Vallard, Alexis; Guy, Jean-Baptiste; Rodriguez-Lafrasse, Claire; Deutsch, Eric; Chargari, Cyrus
Highlights: NP can be used as radio-sensitizers (high Z physical mechanism + biological pathways). NP can be used as drug vectors in radiochemotherapy. NP can have a theranostic utilization: radio-sensitizer + imaging tumour tracker. Today only 8 clinical trials investigate NP possible involvement in radiotherapy area. There are still too few data documenting the toxicity of NP. Abstract: Nanoparticles (NP) are "in vogue" in medical research. Pre-clinical studies accumulate evidence of NP enhancing radiation therapy. On one hand, NP, selected for their intrinsic physicochemical characteristics, are radio-sensitizers. Thus, when NP accumulate in cancer cells, they increase the radiation absorption coefficient specifically in tumour tissue, sparing healthy surrounding tissue from toxicity. On the other hand, NP, by being drug vectors, can carry radio-sensitizer therapeutics to cancer cells. Finally, NP present theranostic effects. Indeed they are used in imaging as contrast agents. NP therefore can be multi-tasking and have promising prospect in radiotherapy field. In spite of the numerous encouraging preclinical evidence, the very small number of clinical trials investigating NP possible involvement in the radiotherapy clinical practice suggests a physicians' unwillingness. Many prerequisites seem necessary including define biological mechanisms of NP radiosensitization pathways and of NP clearance. NP biocompatibility and toxicities should be better investigated to select, among the extensive range of possible systems, the harmless and most efficient one, and to finally come to a safe and successful clinical use. The present review focuses on the various interests of NP in the radiotherapy area and proposes a discussion about their role in the future clinical practice.